Effect of Nurse-Led Education on Knowledge and Self-Management in Patients with Acute Coronary Syndrome and Type 2 Diabetes - Sila Dewi Anggreni; Suhaimi Suhaimi; Lina Erlina; Harmilah Harmilah; Efyra Efyra; Zolla Amely Ilda; Elvi Oktarina; Yosi Suryarinilsih (MEDICA (International Medical Scientific Journal), 2026)
Patients with acute coronary syndrome (ACS) and type 2 diabetes mellitus (T2DM) require effective self-management to reduce complications and recurrent cardiovascular events. However, evidence regarding the effectiveness of structured nurse-led education during hospitalization remains limited. This study evaluated the effect of a structured nurse-led heart and diabetes education program on knowledge and self-management among hospitalized patients with ACS and T2DM. A quasi-experimental one-group pretest–posttest study without a control group was conducted at Dr. M. Djamil General Hospital, Padang, Indonesia, between October and November 2024. Fifty eligible patients participated in a two-session nurse-led educational intervention. Knowledge and self-management were assessed at baseline and seven days after the intervention using validated instruments. Data were analyzed using paired t-tests with 95% confidence intervals and effect size estimation. Knowledge scores increased significantly from 19.96 ± 3.69 to 22.68 ± 1.70 (mean difference = 2.72; 95% CI: 2.02–3.42; p < 0.001; Cohen’s d = 0.94), indicating a large educational effect. Self-management scores also improved significantly from 98.38 ± 15.30 to 100.48 ± 13.32 (mean difference = 2.10; 95% CI: 0.79–3.41; p = 0.002), although the effect size was small (Cohen’s d = 0.15). These findings suggest that structured nurse-led education effectively improves disease-related knowledge and promotes early self-management among hospitalized patients with ACS and T2DM. Integrating structured educational interventions into routine discharge planning may strengthen transitional cardiometabolic care, although randomized controlled trials with longer follow-up are needed to confirm the sustainability of these outcomes.